The Dimensions of Quantitative Research in History - Fogel, Robert William; Bogue, Allan G.; Aydelotte, William Osgood; Aydelotte, William Osgood (Book collections on Project MUSE., 1972)
Nine papers consider problems in American, French, and British history that range from economic history to political behavior and social structure.Originally published in 1972.The Princeton Legacy Library uses the latest print-on-demand technology to again make available previously out-of-print books from the distinguished backlist of Princeton University Press. These editions preserve the original texts of these important books while presenting them in durable paperback and hardcover editions. The goal of the Princeton Legacy Library is to vastly increase access to the rich scholarly heritage found in the thousands of books published by Princeton University Press since its founding in 1905.